The Value of Ureteric Stents in Debulking Surgery for Disseminated Ovarian Cancer. Issue 5 (1st July 2009) - Ang, Christine; Naik, Raj
Abstract : Objectives: To review the value of ureteric catheterization in extensive debulking surgery in women with disseminated ovarian cancer. Methods: Our database was searched for all women who had a laparotomy for advanced stage (stages III and IV) ovarian cancer between January 2001 and December 2007. Women who had the word(s) "ureteric, " "ureter, " "stent, " "stents, " and "stented" either in their operation notes or the multidisciplinary meeting discussions were filtered to identify those who had a ureteric stent inserted. Stents inserted because of excision/injury to ureters with reanastomosis or reinsertion to bladder were excluded. Results: Fourteen out of 442 patients were identified as having a "prophylactic" stent inserted. The mean age of this series of 14 women was 66.6 years. Seven women had ultraradical surgery requiring bowel resection and/or resection of tumor from the bladder. Nine women had a stent inserted because of the presence of a hydroureter, 3 for ureteric stricture and 2 to protect a flimsy or fragile ureter after ureteric dissection and tumor debulking. There were no ureteric complications during the post-operative period. This resulted in 9 (64%) women achieving either complete or optimal cytoreduction of their tumor bulk. Optimal/complete cytoreduction in all stage III/IV cases during this period was 88%. Conclusions: Ureteric silastic stents are relatively easy to insert and pose few immediate and long-term problems. They should be considered in women after extensive pelvic side-wall debulking in an attempt to reduce the risk of postoperative ureteric complications.